2015
DOI: 10.1007/s10895-015-1589-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aminophospholipids in the Formation of Lipid Rafts in Model Membranes

Abstract: The phase separation of aminophospholipids in glycerophospholipid matrix and the effect of cholesterol were studied by means of fluorescence microscopy of giant unilamellar vesicles (GUV). GUVs were composed of binary mixtures, egg yolk phosphatidylcholine (eggPC)/egg yolk phosphatidylethanolamine (eggPE) and egg yolk phosphatidylcholine (eggPC)/brain phosphatidylserine (brainPS), and ternary ones with both aminophospholipids (eggPC/eggPE/brainPS). Gel/liquid-disordered phase coexistence was detected in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, recent studies have demonstrated the expression and functional role of phosphatidylserine at lipid rafts of mammalian plasma membranes. Phosphatidylserine promotes the formation of lipid rafts and low-density liquid-ordered microdomains in physical models of the plasma membranes (22), as well as in plasma membranes of living cells (6), consisting of areas of sphingomyelin in the outer leaflet and PC in concert with phosphatidylserine in the inner leaflet (61). Remarkably, the phospholipid distribution between liquid-ordered raft and liquid-disordered nonraft domains was shown to depend on the method of their isolation, but, with both the detergent-free and the detergent method, phosphatidylserine was recovered with lipid rafts, albeit at rather low concentrations (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated the expression and functional role of phosphatidylserine at lipid rafts of mammalian plasma membranes. Phosphatidylserine promotes the formation of lipid rafts and low-density liquid-ordered microdomains in physical models of the plasma membranes (22), as well as in plasma membranes of living cells (6), consisting of areas of sphingomyelin in the outer leaflet and PC in concert with phosphatidylserine in the inner leaflet (61). Remarkably, the phospholipid distribution between liquid-ordered raft and liquid-disordered nonraft domains was shown to depend on the method of their isolation, but, with both the detergent-free and the detergent method, phosphatidylserine was recovered with lipid rafts, albeit at rather low concentrations (21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the model suggests that in bilayers with outer leaflets rich in sphingolipids and inner leaflets rich in phosphatidylethanolamine, the transverse distribution of cholesterol would vary with its abundance, shifting sharply from outside to inside near the physiologic level in the plasma membrane, ~40 mol%. Supporting this premise is physical evidence that cholesterol strongly interacts with phosphatidylethanolamine at its physiologic plasma membrane concentration . On the other hand, ergosterol does not .…”
Section: Evidence For Excess Cholesterol In the Inner Leafletmentioning
confidence: 99%
“…Supporting this premise is physical evidence that cholesterol strongly interacts with phosphatidylethanolamine at its physiologic plasma membrane concentration. 95,117 On the other hand, ergosterol does not. 95 This challenges the premise that the preponderance of DHE (hence, ergosterol) in the cytoplasmic leaflet of yeast plasma membranes is driven by the phosphatidylethanolamine therein, raising the possibility that another mechanism underlies the inferred ergosterol asymmetry in yeast.…”
Section: Theoretical Studiesmentioning
confidence: 99%